Soil-transmitted helminth infections and nutritional status among children: A systematic review - Fiya Diniarti; Idris Adewale Ahned; Firman Bintara Maju Harianja; Susilawati Susilawati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Backgroound: Helminthiasis remains a significant public health problem among children in developing countries, including Indonesia. The prevalence of helminth infections among elementary school children in Indonesia averages 28.12%, with regional prevalence ranging from 2.5% to 62%. Soil-transmitted helminth infections are still widely reported and may contribute to impaired growth, anemia, and other nutritional disorders. Cases of helminthiasis, particularly ascariasis, among children under five in Seluma, Bengkulu, in 2025 were associated with poor sanitation, poverty, and inadequate living conditions. Purpose: To analyze helminthiasis according to worm species, infection intensity, polyparasitism, and environmental sanitation, as well as its effects on children’s nutritional status. Method: This study used a systematic review design involving scientific articles published in relevant journals. Literature searches were conducted through Google Scholar, PubMed, ScienceDirect, Cochrane, and MDPI using keywords related to helminthiasis, worm species, infection intensity, polyparasitism, environmental sanitation, and children’s nutritional status. Articles that met the inclusion criteria were reviewed descriptively to determine how worm species, infection intensity, polyparasitism, and environmental sanitation were associated with the nutritional status of children. Results: A total of 30 eligible publications addressing worm species, infection intensity, polyparasitism, environmental sanitation, and children’s nutritional status were included in the review. The findings showed that helminth infections were associated with poor nutritional outcomes, including underweight, impaired growth, and an increased risk of stunting and anemia. Conclusion: Helminth infections, particularly those involving Ascaris lumbricoides, Trichuris trichiura, and hookworm, were associated with poorer nutritional outcomes among children. Infection intensity, polyparasitism, poor sanitation, and inadequate hygiene contributed to an increased risk of stunting, wasting, underweight, and anemia. Recommendations: Improving environmental sanitation, strengthening routine deworming programs, increasing hygiene education, and conducting regular screening for helminth infections and nutritional problems are recommended. Further research should also consider socioeconomic, educational, and behavioral factors.